2023
DOI: 10.1111/1365-2745.14110
|View full text |Cite
|
Sign up to set email alerts
|

Plants stand still but hide: Imperfect and heterogeneous detection is the rule when counting plants

Abstract: The estimation of population size and its variation across space and time largely relies on counts of individuals, generally carried out within spatial units such as quadrats or sites. Missing individuals during counting (i.e. imperfect detection) results in biased estimates of population size and trends. Imperfect detection has been shown to be the rule in animal studies, and most studies now correct for this bias by estimating detection probability. Yet this correction remains exceptional in plant studies, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Occupancy models, by contrast, do both, which is why they have become so popular (Guillera-Arroita, 2017). Like other authors (Chen et al, 2009(Chen et al, , 2013Casanovas et al, 2014;Middleton & Vining, 2022;Perret et al, 2023),…”
Section: F I G U R Esupporting
confidence: 55%
See 3 more Smart Citations
“…Occupancy models, by contrast, do both, which is why they have become so popular (Guillera-Arroita, 2017). Like other authors (Chen et al, 2009(Chen et al, , 2013Casanovas et al, 2014;Middleton & Vining, 2022;Perret et al, 2023),…”
Section: F I G U R Esupporting
confidence: 55%
“…Although the sampled area per site was relatively large (500 m 2 ), we had hoped that the generous allowance of survey time would have counter‐balanced this less‐favourable aspect. Instead, the estimated detection probabilities in this study lie very much within reported detection probabilities of mobile organisms like birds (0.26–0.83 in Tyre et al., 2003; 0.03–0.99 in Kéry & Schmidt, 2008; 0.48–0.60 in Bailey et al., 2009) or amphibians (0.34–0.51 in Tyre et al., 2003; 0.33–0.62 in Bailey et al., 2009) and sessile organisms like plants (0.26–0.57 in Al‐Chokhachy et al., 2013; 0.44–0.74 in Perret et al., 2023), and they were lower than those reported for wood‐dwelling fungi from sites of similar size (0.79–0.94 in Moor et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants sometimes lack key taxonomic features needed for confident in situ identification, making field experience valuable, particularly for recognizing non‐reproductive individuals, such as seedlings or adults outside their flowering seasons. However, the ‘botanist effect’, where experts are assumed to detect more species than non‐experts (Ahrends et al., 2011), may be context‐dependent and could be more influenced by observation time or a surveyor's familiarity with the ecosystem (Morrison, 2016; Perret et al., 2023). To enhance detection rates and efficiency, future post‐disturbance surveys would ideally require participation by expert botanists, either as survey leaders or as trainers for other observers and there is scope for further work on exploring how expertise influences detection rates in these unique systems (e.g., McCarthy et al., 2013).…”
Section: Discussionmentioning
confidence: 99%